Reconstructing Resilient Communities after the Wenchuan Earthquake: Disaster Recovery in China - Otani, Junko (Lexington Books, 2023)
Reconstructing Resilient Communities after the Wenchuan Earthquake: Disaster Recovery in China looks at the changes in Chinese society following the 2008 earthquake in Sichuan from various perspectives ranging from reconstruction policy, mental care for disaster victims, tourism in disaster areas, ethnic minorities, and disaster prevention education. The Wenchuan Earthquake, which occurred three months prior to the Beijing Olympics, attracted worldwide attention in May of 2008. Following this natural disaster, the government in China conducted a delicate bargaining between government top-drown control and openness to its people and the international society in its effort to steer the reconstruction. This book examines the globalization of modern society through examination of these events and considers what we have learned from this disaster, subsequent reconstruction, and issues that may arise in the future.